Ontological Landscapes : Recent Thought on Conceptual Interfaces Between Science and Philosophy. - Petrov, Vesselin (De Gruyter, 2011)
In the last decades ontology has been successfully developed in many directions and has fostered various approaches for depicting the contemporary ontological landscapes. An important task is to outline recent thought on the conceptual interfaces between science and philosophy. The present volume opens up a view onto the plurality of different ontological schemes. The papers collected here discuss the interfaces between ontology and empirical research that are created by the notions of a whole, a thought, a number, a quality, an ability, a kind, notions of causation, dynamicity, and social obj.